2007
DOI: 10.1038/nature05603
|View full text |Cite
|
Sign up to set email alerts
|

eIF4E function in somatic cells modulates ageing in Caenorhabditis elegans

Abstract: Regulation of protein synthesis is critical for cell growth and maintenance. Ageing in many organisms, including humans, is accompanied by marked alterations in both general and specific protein synthesis. Whether these alterations are simply a corollary of the ageing process or have a causative role in senescent decline remains unclear. An array of protein factors facilitates the tight control of messenger RNA translation initiation. The eukaryotic initiation factor 4E (eIF4E), which binds the 7-monomethyl gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
335
1
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 322 publications
(368 citation statements)
references
References 32 publications
16
335
1
8
Order By: Relevance
“…Under reduced nutrient conditions, such as amino acid limitation, TOR activity is quenched, the TOR effectors S6K and 4E-BP are dephosphorylated and consequently protein synthesis decreases. Reduction of mRNA translation by conditions that shift cells from states of nutrient utilization and growth to states of cell maintenance has been shown to increase lifespan of yeast, worm, flies and mice (Hansen et al, 2007;Harrison et al, 2009;Kapahi et al, 2004;Pan et al, 2007;Syntichaki et al, 2007).…”
Section: Tor Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Under reduced nutrient conditions, such as amino acid limitation, TOR activity is quenched, the TOR effectors S6K and 4E-BP are dephosphorylated and consequently protein synthesis decreases. Reduction of mRNA translation by conditions that shift cells from states of nutrient utilization and growth to states of cell maintenance has been shown to increase lifespan of yeast, worm, flies and mice (Hansen et al, 2007;Harrison et al, 2009;Kapahi et al, 2004;Pan et al, 2007;Syntichaki et al, 2007).…”
Section: Tor Signallingmentioning
confidence: 99%
“…Worms bearing mutations in S6K (RSKS-1) and components of the translational machinery such as ribosomal proteins and translation initiation factors, live longer (Hansen et al, 2007;Kaeberlein and Kennedy, 2008;Syntichaki et al, 2007). Recently, TORC2 has been implicated in regulation of worm longevity (Soukas et al, 2009).…”
Section: Tor Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant negative forms of TOR or its downstream effector S6K1 or overexpression of the upstream inhibitors of TOR, TSC1 and TSC2, extend lifespan in Drosophila (Kapahi et al, 2004). Similarly, deletion of TOR1 and many of its downstream targets in yeast (Kaeberlein et al, 2005) or deletion of the downstream TOR target e1F4E in worms confers longevity (Syntichaki et al, 2007).…”
Section: Mtormentioning
confidence: 99%
“…Similarly, Pan et al (2007) showed that mRNA translation exerts pleiotropic effects on growth, reproduction, stress resistance and lifespan in C. elegans. The Tavernarakis lab (Syntichaki et al, 2007) showed that loss of a specific eIF4E isoform (IFE-2) functions in somatic tissues, reduces global protein synthesis, protects from oxidative stress and extends lifespan (the eukaryotic initiation factor 4E (eIF4E) is a principal regulator of protein synthesis). Lifespan extension is independent of the forkhead transcription factor DAF-16.…”
Section: The Search For More Longevity Genesmentioning
confidence: 99%